The Influence of Technological Skills, Ease of Use, and Service Security Regarding M-Banking BCA User Satisfaction among Students Faculty of Economics and Business UPN "Veteran" East Java - Yulianto, M. Efendy Dwi; Anwar, Muhadjir (International Journal of Economics (IJEC), 2024)
Currently is an era where various kinds of technology are developing. Mobile Banking is a technology created by a banking company which is usually called M-Banking. M-Banking is a service provided by banks to their customers to carry out various banking transactions by sharing the features and menus found in banking applications via smart phones or smartphones. The aim of this research is to explain the influence of technological skills, ease of use, security of services on satisfaction using BCA M- Banking among students at the economics and business faculty of UPN "Veteran" East Java. This research uses a quantitative approach through purposive sampling techniques. The population in this study were students from the economics and business faculty of UPN "Veteran" East Java. The samples in this research are active students studying at the Faculty of Economics and Business, UPN "Veteran" East Java, students from the Faculty of Economics and Business, UPN "Veteran" East Java who have BCA M-Banking. Meanwhile, the sample in this study was 130 respondents from the economics and business faculty of UPN "Veteran" East Java with relevant criteria. All tests carried out using the Smart PLS Application indicate that all tests received scores above the prerequisite values so that the tests were said to be reliable. The research results indicate that Technology Skills have a positive and significant effect on Customers Satisfaction. Ease of Use has a positive and significant effect on Customers satisfaction, US well US Service Security has a positive and significant effect on Customers Satisfaction.